Corporate board heterogeneity and operations cost in the industrials sector of the Johannesburg Stock Exchange - Simon-Ilogho, Busola Elizabeth (International Journal of Management and Sustainability, 2025)
This study explores the influence of corporate board diversity on operational costs in South Africa's industrial sector, focusing on companies listed on the Johannesburg Stock Exchange (JSE). The research examines the relationship between board diversity in terms of gender, ethnicity, nationality, age, and operational costs, which significantly affect a firm's profitability. By applying a positivist research methodology involving deductive reasoning, the study analyzes the causal effect of board diversity using quantitative data from a 10-year panel dataset, covering 2014 to 2023, of 26 JSE-listed industrial firms' annual reports. The findings confirm that nationality and age diversity do not significantly impact operational costs, although operating expenses are positively influenced by board members aged between 50 and 59 years, indicating that this age range is associated with increased operating expenses. Among other insights, the study suggests that board diversity influences operating costs, though the effect is nuanced and depends on the specific composition of the board. The research emphasizes the importance of operational costs in maintaining profitability, recommending that firms seek an optimal balance of board diversity and operational efficiency. It also advocates that board member selection should prioritize competence and experience over identity politics.